Embryonic stem cell-like subpopulations are present within Schwannoma. (November 2020) - Kilmister, Ethan J.; Patel, Josie; Bockett, Nicholas; Chang-McDonald, Bridget; Sim, Dalice; Wickremesekera, Agadha; Davis, Paul F.; Tan, Swee T.
Highlights: Induced pluripotent stem cell (iPSC) markers OCT4, SOX2, NANOG, KLF4 and c-MYC are expressed in Schwannoma. The endothelium of the tumor microvessels of Schwannoma that express iPSC markers displays an endothelial progenitor cell phenotype. We demonstrate two embryonic stem cell-like subpopulations: an OCT4+/SOX2+/NANOG+/KLF4+/c-MYC+/CD133+ subpopulation on the endothelium of tumor microvessels, and an OCT4-/SOX2+/NANOG-/KLF4+/c-MYC+/CD133+ subpopulation within Schwannoma. Abstract: Background: There is accumulating evidence of the presence of embryonic stem cell (ESC)-like cells in benign tumors. Aim: This study aimed to identify ESC-like cells in Schwannoma using the induced-pluripotent stem cell (iPSC) markers OCT4, SOX2, NANOG, KLF4 and c-MYC. Methods: Immunohistochemical (IHC) staining (n = 20) and RT-qPCR (n = 6) were performed on Schwannoma tissue samples (STS) to investigate protein and mRNA expression of these iPSC markers, respectively. Immunofluorescence (IF) staining was performed to investigate co-localization of the iPSC markers with CD34, α-SMA and CD133. Results: IHC staining and RT-qPCR demonstrated protein and mRNA expression of all five iPSC markers, respectively. IF staining showed expression of SOX2, KLF4 and c-MYC on the tumor cells and the endothelium of the tumor microvessels which also expressed OCT4, while NANOG was exclusively expressed on the endothelium of the tumor microvessels. The OCT4+/CD34+ endothelium expressed CD133. Conclusion: We have identified a putative OCT4+/SOX2+/NANOG+/KLF4+/c-MYC+/CD133+ ESC-like subpopulation on the endothelium of tumor microvessels and an OCT4-/SOX2+/NANOG-/KLF4+/c-MYC+/CD133+ ESC-like subpopulation, within Schwannoma.